1997
DOI: 10.1021/ac960673t
|View full text |Cite
|
Sign up to set email alerts
|

Space Charge Evaluation in a Plasma-Source Mass Spectrograph

Abstract: Space charge effects, and the matrix interferences they cause, are problems in inductively coupled plasma mass spectrometry (ICPMS). It has previously been observed that these deleterious space charge effects are not significantly present in sector-field instruments, a fact that has been attributed, but not demonstrated, to the high accelerating potentials they commonly employ. To examine the significance of space charge in our plasma-source mass spectrograph (which operates at only moderate accelerating poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
18
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 20 publications
4
18
0
Order By: Relevance
“…With this approach, the isotope-ratio precision worsens to 9.7% RSD, and so demonstrates how simultaneous multi-element detection improves precision. The observed isotope ratio of 65 Cu : 63 Cu is 0.466, 0.02 above the expected isotope ratio of 0.446; 52 this discrepancy is most likely due to mass bias in ion sampling from the ICP, 53,54 and is consistent with our previous solution-sample-introduction ICP-DOFMS studies.…”
Section: Isotope-ratio Analysis By La-icp-dofmssupporting
confidence: 87%
“…With this approach, the isotope-ratio precision worsens to 9.7% RSD, and so demonstrates how simultaneous multi-element detection improves precision. The observed isotope ratio of 65 Cu : 63 Cu is 0.466, 0.02 above the expected isotope ratio of 0.446; 52 this discrepancy is most likely due to mass bias in ion sampling from the ICP, 53,54 and is consistent with our previous solution-sample-introduction ICP-DOFMS studies.…”
Section: Isotope-ratio Analysis By La-icp-dofmssupporting
confidence: 87%
“…Previous studies proposed that mass bias in ICP‐MS could originate in the sample introduction and transportation processes, and different processes occurring in the ICP . The space‐charge effect is often considered as a dominant factor in causing instrumental mass bias because of the preferential transmission of heavier ions . A previous study also implied that any factors affecting plasma stability could cause variation in the instrumental mass bias .…”
Section: Discussionmentioning
confidence: 99%
“…Because a sector-field mass spectrometer produces spectral features that become closer and closer together at higher masses, isotopic peaks at the upper end of the atomic mass range were impossible to resolve when the electro-optic imaging detector (EOID) was used. [72][73][74] This performance limitation was underscored and clarified by David Solyom, a graduate student who assumed the project after Tom Burgoyne received his doctorate. [75][76][77] As importantly, Solyom showed that the instrument, when tuned properly and fitted with a single-channel detector, could achieve resolution that was more than adequate, even at the highest atomic masses.…”
Section: Array Detector Atomic Mass Spectrometer (Adams)mentioning
confidence: 99%